Potential applications of focused ultrasound for spinal cord diseases: a narrative review of preclinical studies - Ryan Nguyen; Victor Gabriel El-Hajj; Umberto Battistin; Karl J. Habashy; Victor E. Staartjes; Adrian Elmi-Terander; Jingke Zhang; Abdul Karim Ghaith (Brain and Spine)
Focused ultrasound (FUS) technology provides unique advantages as a therapy targeting the central nervous system (CNS). We aimed to investigate and summarize the potential applications of FUS in the context of spinal cord diseases. Search strategies were created using a combination of keywords and standardized index terms. Searches were run in April 2025 in the Ovid Cochrane Central Register of Controlled Trials, EBSCO MegaFILE, Ovid Embase, Ovid Medline, Ovid PsycINFO, Scopus, and Web of Science Core Collection to retrieve all relevant studies from inception until 2024. A narrative and comprehensive summary of the current body of evidence was performed. Current preclinical studies indicate the potential use of spinal cord FUS in blood-spinal cord barrier (BSCB) disruption, neuromodulation, and inflammatory regulation following spinal cord injury. Targeted CNS drug delivery with BSCB disruption using FUS has proven promising in the context of neuro-oncology and neurotrauma. Additionally, FUS has been explored for neuromodulation in managing neuropathic pain and spasticity. FUS to the spinal cord may also provide anti-inflammatory effects and alter the local cellular response to injury. While therapeutic FUS ablation of brain structures has been extensively studied, research on similar applications within the spinal cord was less prevalent and faces multiple challenges. FUS is a highly promising technique with multiple advantages and potential applications in the treatment of spinal cord diseases. Current research efforts have shifted focus towards translational studies, while human trials are currently limited.